Collocation method applied to unsteady flow of gas through a porous medium - Upadhyay, Subrahamanyam; Rai, K.N. (International Journal of Applied Mathematical Research, 2014)
In this article, we study a two point boundary value problem of non linear differential equation on a semi infinitedomain that describes the unsteady flow of gas through a porous medium. Under special transform, we convert thisproblem to boundary value problem in compactly supported domain [0,1]. An algorithm provided for obtainingsolution by Legendre wavelet collocation method. This method is effectively used to determine y (t) and its initialslope at the origin. The convergence and stability analysis is provided. The results thus obtained are compared withthe those obtained from modified decomposition method [5], Variational iterational method [6], rational Chebyshevfunctions method (RCM) [7] and radial basis function (RBF) collocation method [10]. It has been observed thatthe proposed method provide better results with lesser computational complexity.Keywords: Convergence and stability analysis, Legendre Wavelets, Legendre wavelet collocation method, Kidder's equation.